2018
DOI: 10.1016/j.physleta.2018.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Mutual-friction induced instability of normal-fluid vortex tubes in superfluid helium-4

Abstract: It is shown that, as a result of its interactions with superfluid vorticity, a normal-fluid vortex tube in helium-4 becomes unstable and disintegrates. The superfluid vorticity acquires only a small (few percents of normal-fluid tube strength) polarization, whilst expanding in a front-like manner in the intervortex space of the normal-fluid, forming a dense, unstructured tangle in the process. The accompanied energy spectra scalings offer a structural explanation of analogous scalings in fully developed finite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…They should melt, changing into a highly irregular structure. Other example is a series of numerical simulations by Kivotides [13], [14], [15], [16]), who studied the exact (not HVBK) dynamics of quantum vortices in the turbulent flows (at finite temperature) and concluded "that the results do not show that a turbulent normal-fluid with a Kolmogorov energy spectrum induces superfluid vortex bundles in the superfluid". In paper [15] Kivotides reported about observation of clusters with weakly polarized vortex lines and associated Kolmogorov -type spectra E(k) ∝ k 5/3 .…”
Section: Hvbk Approach a Hvbk Approach For Rotating Superfluidsmentioning
confidence: 99%
“…They should melt, changing into a highly irregular structure. Other example is a series of numerical simulations by Kivotides [13], [14], [15], [16]), who studied the exact (not HVBK) dynamics of quantum vortices in the turbulent flows (at finite temperature) and concluded "that the results do not show that a turbulent normal-fluid with a Kolmogorov energy spectrum induces superfluid vortex bundles in the superfluid". In paper [15] Kivotides reported about observation of clusters with weakly polarized vortex lines and associated Kolmogorov -type spectra E(k) ∝ k 5/3 .…”
Section: Hvbk Approach a Hvbk Approach For Rotating Superfluidsmentioning
confidence: 99%
“…Indeed, it was shown that, under typical conditions, normal-fluid inertia overpowers the mutual-friction force, hence, the latter cannot efficiently correlate superfluid vorticity with the normal-fluid one. In a similar vein, it was shown that, as a result of its interactions with ambient quantized vortices, a straight normal-fluid tube becomes unstable, and only a small percentage of generated superfluid vorticity is eventually trapped by the unstable normal tube mimicking its structure[20]. Instead, the majority of superfluid vorticity propagates in the intervortex space.…”
mentioning
confidence: 94%
“…In other words, the normal-fluid and superfluid vortex structures are locally different from each other. The crucial role of flow instabilities in this phenomenology has been indicated in reference [20].…”
mentioning
confidence: 94%
See 1 more Smart Citation